Sleep problems and the associative factors among Kadazandusun elderly in kampung Ramayah - Juniah, Colman (University Malaysia Sarawak, UNIMAS., 2010)
The objective of this study is to examine the prevalence of sleep problems among Kadazandusun elderly who lived in Kampung Ramayah and its association factors contributing to sleep problems